The role of professional association in developing teacher performance on ELT (a study on APSPBI) - Darwin (Universitas Madako Tolitoli, 2024)
The field of English Language Teaching (ELT) is rapidly evolving, demanding English teachers to continuously update their competencies in order to meet new pedagogical challenges and expectations. In this dynamic context, professional development cannot be achieved solely through individual effort; rather, it requires collaborative engagement through communities or professional associations where teachers can exchange ideas, share best practices, and receive ongoing support. This small-scale survey research was conducted to explore alternative strategies for professional development, particularly through the role of teacher associations. The participant of this study was a member of the Association of English Language Education Study Programs in Indonesia (APSPBI), selected using purposive sampling. Data were collected through an online semi-structured interview and analyzed using descriptive statistical techniques. The findings revealed that APSPBI regularly organizes a range of academic and professional activities such as workshops, webinars, conferences, and collaborative research initiatives that significantly contribute to the continuous professional growth of ELT practitioners. These activities not only enhance teachers' pedagogical knowledge and classroom practices but also foster networking, innovation, and reflective teaching. The results of this study indicate that APSPBI serves as an effective platform for English teachers seeking sustainable and collaborative professional development. Thus, APSPBI may be considered a viable alternative professional community that supports the advancement of teacher professionalism in the field of ELT, particularly in the Indonesian context. Further studies involving larger samples are recommended to explore the broader impact of teacher associations on instructional quality and student outcomes